The The Influence of The Development of Cashless Payment on The Effectiveness of Payments Among IPIEF Students Batch 2020 - Ariba, Baarik; Wiranatakusuma, Dimas Bagus; Hafidhi, Ilham (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Cashless payment methods are not new in our country. there are many media and organizational structures or agencies that use cashless transactions. Cashless payment is a payment without the use of cash in the transaction. Knowing that today many have used these transactions, both from the user and operator side, the author is interested in discussing these transactions in everyday life related to the convenience that causes users and organizers to use this transaction. This study discusses the use of cashless payments among students, especially IPIEF 2020 students. The author uses a qualitative method by conducting interviews with all IPIEF 2020 students regarding the use of cashless payments and also the intensity of their use. The author conducted interviews using whatsapp voice call. In this way, the author finds several reasons why there are so many and high intensity of cashless payment usage among IPIEF 2020 students. The majority of interview participants have known and used cashless payments with high intensity, this is in line with the author's analysis, namely because it is convenience that causes this.